CALOCUBE: an approach to high-granularity and homogenous calorimetry for space based detectors. (13th February 2015) - Bongi, M; Adriani, O; Albergo, S; Auditore, L; Bagliesi, M G; Berti, E; Bigongiari, G; Boezio, M; Bonechi, L; Bonechi, S; Bonvicini, V; Bottai, S; et al.
Abstract: Future space experiments dedicated to the observation of high-energy gamma and cosmic rays will increasingly rely on a highly performing calorimetry apparatus, and their physics performance will be primarily determined by the geometrical dimensions and the energy resolution of the calorimeter deployed. Thus it is extremely important to optimize its geometrical acceptance, the granularity, and its absorption depth for the measurement of the particle energy with respect to the total mass of the apparatus which is the most important constraint for a space launch. The proposed design tries to satisfy these criteria while staying within a total mass budget of about 1.6 tons. Calocube is a homogeneous calorimeter instrumented with Cesium iodide (CsI) crystals, whose geometry is cubic and isotropic, so as to detect particles arriving from every direction in space, thus maximizing the acceptance; granularity is obtained by filling the cubic volume with small cubic CsI crystals. The total radiation length in any direction is more than adequate for optimal electromagnetic particle identification and energy measurement, whilst the interaction length is at least suficient to allow a precise reconstruction of hadronic showers. Optimal values for the size of the crystals and spacing among them have been studied. The design forms the basis of a three-year R&D activity which has been approved and financed by INFN. An overall description of the system, as well as results from preliminary tests on particle beams will be described.